Reason behind wet pack after steam sterilization and its consequences: An overview from Central Sterile Supply Department of a cancer center in eastern India - Debabrata Basu (Elsevier, 2017)
Summary: Wet pack after steam sterilization process that means there are surely obtain millions of microorganisms that can breed and multiply rapidly and objects are unsterile and can never be used for further procedure.There are many reasons behind the wet pack occurrences after autoclaving like poor quality of wrapping materials, faulty valves of rigid container, faulty loading and packaging technique, poor steam quality, sterilizer malfunction and may be design related problems in CSSD sterile storage area.Cause of wet pack after steam sterilization processes may occur severe problems because of wasted time and effort, increased work load, increased cost, potentially contaminated instruments, infection risk to the patient, poor patient outcomes and delayed or cancellation of procedures.But such wet pack scenario can be avoided by various methods by using good steam (water) quality, performing periodic maintenance of the Autoclaves, avoidance of sterilizer overloading, allowing adequate post sterilization time to cool down the materials to room temperature, using good quality wrapping materials, properly maintain temperature and humidity of sterile storage area etc. Keywords: Root cause of wet pack, Consequences of wet pack, Cost complications, Prevention, Conclusion